Hadith Interpretation in Contemporary Acehnese Sufism: A Hermeneutic Analysis of Abuya Amran’s Texts - Sulidar Sulidar; Mawardi Mawardi; Ishak Sulaiman (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2026)
Despite growing scholarship on Acehnese Sufism, the textual practice of hadith reading within local Sufi communities has received little systematic analysis, as prior studies have privileged sociological or normative approaches over literary and hermeneutic ones. Drawing on living text theory and Sufi hermeneutics, this study examines how hadith are selected, structured, interpreted, and transmitted within contemporary Acehnese Sufism through Abuya Amran's corpus. Using qualitative library research with textual and hermeneutic analysis, we analyzed 30 documents produced by Abuya Amran and the MPTTI community (1998–2024), identifying 21 hadith fragments and subjecting 17 foundational hadith to systematic takhrij. Five dominant interpretive patterns emerged: isyari (symbolic-inner), moral-ethical, ma'rifat-analogical, narrative-illustrative, and praxis-command, all oriented toward irfānī (ethical-spiritual) meaning rather than sanad criticism or fiqh normativity. This study makes two original contributions: it demonstrates that hadith authority in this tradition is constituted through pedagogical function rather than transmission chains, and it establishes a living-text model for analyzing hadith as dynamic religious literature, an analytical framework absent from existing Nusantara Sufi scholarship.